Spatial distribution and determinants of limited access to improved drinking water service among households in Ethiopia based on the 2019 Ethiopian Mini Demographic and Health Survey: spatial and multilevel analyses - Alemayehu, Meron Asmamaw; Agimas, Muluken Chanie; Shewaye, Daniel Alayu; Derseh, Nebiyu Mekonnen; Aragaw, Fantu Mamo (Frontiers in Water, 2023)
Introduction: Safe and easily accessible drinking water service generates substantial benefits for public health and the economy. About 10% of the global burden of disease worldwide could be prevented with improved access to drinking water. The death of approximately 30% of under five children in developing countries is attributable to inadequate access to improved drinking water. The importance of up-to-date evidence for actions regarding the distribution of access to improved drinking water services in Ethiopia was emphasized. Therefore, this study aimed to explore the spatial distribution and determinants of limited access to improved drinking water service among households in Ethiopia. Methods: This study used the 2019’s Ethiopian Mini Demographic and Health Survey data. The data were weighted using sampling weight to restore the representativeness and to get valid statistical estimates. After excluding ineligible households, a total weighted sample of 5,760 households was included in the final analysis. The analysis was performed using STATA v 14.2, ArcGIS Pro, and SaTScan version 10.1 software. To find significant determinants with limited access to improved drinking water service, we used a multilevel logistic regression model. P-value <0.05 was used to declare statistical significance. Results: This study found that in Ethiopia, 16.1% (95% CI: 15.2, 17.1) of households have limited access to improved drinking water services. The spatial distribution of households with limited access was identified to be clustered across a few regions of the country (Moran’s I = 0.17, p-value <0.01). The most likely significant primary clusters with highly limited access were seen in the Somali region, the border between Amhara and Afar region, the border between Oromia and Afar region, and the northeastern Tigray region. Wealth index, Age, residence, and region were significantly associated with limited access to improved drinking water service. Conclusion: Limited access to improved drinking water service in Ethiopia varies across regions and there exists within the country inequality in the service provision. Prioritization and extra level of efforts should be made by concerned government and non-government organizations as well as other stakeholders for those underprivileged areas and groups of the population as they are found in the study.